2021
DOI: 10.2337/db21-0261
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplets Protect Human β-Cells From Lipotoxicity-Induced Stress and Cell Identity Changes

Abstract: Supplemental Figures and Legends Supplemental Figure 1. PLIN2KD significantly altered TGFβ/SMAD pathway genes. (A) Heat maps showing significantly elevated levels of TGFβ/SMAD pathway-related genes in PLIN2KD EndoCβH2-Cre β cells. The color keys represent the row-wise Z-score. (B) Notably, GDF15 level appears to be PLIN2 dependent (directly extracted from bulk RNA-seq data), TPM: Transcripts Per Million. All error bars indicate SD, n=3, * P<0.05 vs Sham. Supplemental Figure 2. NAC cannot rescue EA induced effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Downregulation of perilipin 2 (PLIN2), which is a key scaffold protein and resides on the surface of LDs, ameliorates the effects of fatty acid-and chemical-induced ER stress, whereas PLIN2 overexpression exacerbates them (38). Contrary to that report, the other studies showed that downregulation of PLIN2 reduced the levels of FFAs incorporated into LD and resulted in mitochondrial dysfunction (39) and endoplasmic reticulum (ER) stress (40), as LD formation protects cells against toxic effects of FFA (41). In any case, excess LD accumulation may reflect inappropriate lipid metabolism beyond FFA homeostasis, which causes lipotoxicity-induced endoplasmic reticulum stress, resulting in impaired insulin granule maturation and decreased insulin secretory capacity (42,43).…”
Section: Discussionmentioning
confidence: 84%
“…Downregulation of perilipin 2 (PLIN2), which is a key scaffold protein and resides on the surface of LDs, ameliorates the effects of fatty acid-and chemical-induced ER stress, whereas PLIN2 overexpression exacerbates them (38). Contrary to that report, the other studies showed that downregulation of PLIN2 reduced the levels of FFAs incorporated into LD and resulted in mitochondrial dysfunction (39) and endoplasmic reticulum (ER) stress (40), as LD formation protects cells against toxic effects of FFA (41). In any case, excess LD accumulation may reflect inappropriate lipid metabolism beyond FFA homeostasis, which causes lipotoxicity-induced endoplasmic reticulum stress, resulting in impaired insulin granule maturation and decreased insulin secretory capacity (42,43).…”
Section: Discussionmentioning
confidence: 84%
“…In agreement with our results, previous studies [ 13 , 30 ] have reported a time-dependent formation of LD in rodent β-cells co-treated with palmitate and oleate. Furthermore, others have observed LD in the cytoplasm of EndoC-βH1/2 cells following prolonged exposure to palmitate [ 30 , 31 ]. Interestingly, the overexpression of LD-associated proteins, PLIN1 and PLIN5, has been shown to protect rodent β-cell function and viability during exposure to exogenous palmitate via an increase in FFA oxidation and a decrease in ER stress [ 15 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While exploring the role of the perilipin family in regulating the ISCs phenotype, we first found Pparγ and perilipin proteins, especially PLIN2, to be associated with decreased functional LDs active metabolites levels, which serve as key molecular events for lipotoxicity-driven ISCs activation. Recently, the protective effect of Plin2 in human β cells against lipotoxic-induced cellular autophagic flux and reduces endoplasmic reticulum stress has been reported [ 15 , 16 , 36 ]. Plin2 overexpression restored the polygonal appearance of quiescent ISCs with LDs re-formation and reduced the activation degree and ECM synthesis, producing a resting-state phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the pancreas, the majority of islet neutral lipid staining was shown to co-localize with PLIN2 and PLIN3 in human adult normal and T2DM patients [ 15 ]. Recently, Roland Stein et al found [ 16 ] glucose-stimulated insulin secretion was blunted in Plin2 knockdown EndoC- β H1 cells and improved in Plin2 overexpression cells, suggesting LD accumulation regulated by perilipin levels is a critical signaling molecule to impact islet cell activity. However, the role of perilipin family in regulation of the ISC phenotype is unclear.…”
Section: Introductionmentioning
confidence: 99%